Intrinsic cancer vaccination - Yang, Yoosoo; Nam, Gi-Hoon; Kim, Gi Beom; Kim, Yoon Kyoung; Kim, In-San (ELSEVIER, 2019)
Immunotherapy is revolutionizing the treatment of cancer, and the current immunotherapeutics have remarkably improved the outcomes for some cancer patients. However, we still need answers for patients with immunologically cold tumors that do not benefit from the current immunotherapy treatments. Here, we suggest a novel strategy that is based on using a very old and sophisticated system for cancer immunotherapy, namely "intrinsic cancer vaccination", which seeks to awaken our own immune system to activate tumor-specific T cells. To do this, we must take advantage of the genetic instability of cancer cells and the expression of cancer cell neoantigens to trigger immunity against cancer cells. It will be necessary to not only enhance the phagocytosis of cancer cells by antigen presenting cells but also induce immunogenic cancer cell death and the subsequent immunogenic clearance, cross-priming and generation of tumor-specific T cells. This strategy will allow us to avoid using known tumor-specific antigens, ex vivo manipulation or adoptive cell therapy; rather, we will efficiently present cancer cell neoantigens to our immune system and propagate the cancer-immunity cycle. This strategy simply follows the natural cycle of cancer-immunity from its very first step, and therefore could be combined with any other treatment modality to yield enhanced efficacy. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: IMMUNOGENIC CELL-DEATH; BACILLUS-CALMETTE-GUERIN; MHC CLASS-I; MITOCHONDRIAL TRANSCRIPTION FACTOR; PATTERN-RECOGNITION RECEPTORS; IMMUNE CHECKPOINT BLOCKADE; MEMORY T-CELLS; DENDRITIC CELLS; TUMOR MICROENVIRONMENT; CALRETICULIN EXPOSURE